COVID-19 Vaccination Rollout: Aspects of Acceptability in South Africa - Bent Steenberg; Nellie Myburgh; Andile Sokani; Nonhlanhla Ngwenya; Portia Mutevedzi; Shabir A. Madhi (Vaccines, 2022)
Unprecedented in scale, immense COVID-19 immunization programs have been rolled out globally. This article explores aspects of hypothetical vaccine acceptability in Soweto, South Africa, shortly before such vaccines became available. Whereas hypothetical acceptance was normative, this has not translated into uptake today, which remains concerningly low in South Africa, especially in Soweto. For that reason, we mobilize anthropological concepts to analyze acceptance, hesitancy, and denial to gauge public proclivity to inoculate. We found that COVID-19′s haphazard mediatization generated a ‘field of suspicion’ towards authorities and vaccination, which, amplified by dis- and misinformation, fostered othering, hesitancy, and denialism considerably. Further, we demonstrate that stated intent to immunize cannot be used to predict outcome. It remains paramount during vaccination rollouts to unveil and address aspects detrimental to vaccine confidence and selectivity, especially in lower-income groups for underlying context-specific cultural, spiritual, historical, and socioeconomic reasons. Appropriate mediazation alongside a debunking of counterfactual claims is crucial in driving forward immunization.